How It Works Tractor - Hepworth, Amelia; Semple, David, (Illustrator) (Wilton, CT : Tiger Tales, 2021)
"Beep! Beep! Follow the busy tractor around the farm in this super simple first introduction to tractors. With layered die-cuts, fun facts and a mouse to spot on every spread!"--.
Cover title.
On die-cut board pages.
"Originally published in Great Britain 2021 by Little Tiger Books Ltd."--Page 4 of cover.
new kids book 2023 fall.
AD550L
Decoding demand: 80 (high) Semantic demand: 75 (high) Syntactic demand: 73 (high) Structure demand: 79 (high)
Keywords: Tractors -- Juvenile literature; Farm life -- Juvenile literature; Board books; Toy and movable books; Board books